Time planning and academic performance in Ritman university, Ikot Ekpene, Akwa Ibom state, Nigeria (Singaporean Journal of Business Economics and Management, 2023)
The study examined the relationship between time planning and academic performance in Ritman University, Ikot Ekpene, Akwa Ibom State. A survey research design was adopted for the study. A sample of 228 respondents was drawn from a population of 600 using Taro Yamane's scientific sampling technique. For the objectives of the study to be achieved, four hypotheses were formulated and tested. The study utilized structured questionnaire and interview as major instruments for data collection. 240 questionnaires were distributed and 228 were usably returned. Data collected were analyzed using simple percentage and ordinal logistic regression. Results showed that, all the independent variables maintained insignificant relationship with academic performance in Ritman University, Ikot Ekpene, Akwa Ibom State. It was recommended that, students should have realistic expectations, which can decrease pressure, stress, anxiety and imbalance sense of well-being for them to perform at their best academically, students should avoid distracting factors such as noise or visual stimuli, or internal factors, such as thoughts or emotions whether from multitasking, technological devices, environmental factors, or non-academic activities for effective academic performance, students should manage interruptions effectively through good communication skills, planning, and the ability to prioritize tasks and activities. Finally, it was recommended that students should avoid procrastination by timely task completion, decreased stress levels, increased motivation and proper time planning management toachieve academic goals.